A Cognitive Linguistic Study of Silence/Pause-Based Incongruities in Selected Instances from Mind Your Language's Sitcom Series - H. Al-Bahrani, Rana (Journal of College of Education, 2018)
The present research aims at: First, to examine the reasons behind using silence/pause-based unintentional incongruities in selected instances from the British Sitcom Mind Your Language; second, to explore specifically the types of silence/pause-based unintentional incongruities and the different facial gestures that accompany each of these types. To meet these two objectives, the analysis will be theoretically and conceptually-based, respectively. Conclusions, as far as the first objective is concerned, have shown that silence can be used to reflect: the sense of being inattentive; lack of understanding; being unfamiliar with what one hears; the time needed for thinking and associating, and the act of hiding one's nervousness, etc. As for pause, it is used for reflecting the sense of being confused; indicating that there is an interrupting event; and giving time to oneself to comprehend, re-consider, and correct what one has said, etc. As for the second objective, it has been concluded that silence appears to have the four categories cited by Kostiuk (2012); these included the structural, reflexive, tactical, and ignorant types of silence. Pauses, on the other hand, have only three categories: tactical, structural, and reflexive. Speaking of the reactions and facial expressions that accompany silence when encountering unintentionally incongruous events, they include the following: closing one's eyes, and feeling amazed, proud, shocked, and speechless, etc. whereas those that accompany pause are: feeling confused, asking a question for clarification, and opening one's mouth, etc.
Keywords: silence, pause, incongruity, resolution, reflective silence, tactical silence